Dr. Anderson's high-fiber fitness plan - Anderson, James W. (University Press of Kentucky, 1994)
This pioneering work by internationally known physician Dr. James W. Anderson is a quick and easy guide to a healthier lifestyle. Breaking the steps to healthful living into manageable units, Dr. Anderson shows how making the right choices in diet, exercise and relaxation can improve health and reduce risks of major disease. Dr. Anderson's High-Fiber Fitness Plan is an essential handbook for those who want a hassle-free way to fitness and health. It has an enclosed spiral binding that lies flat on the counter with a wipeable cover and plenty of space for notes. The first half of the book is fi.